Submarine Outfalls of Treated Wastewater Effluents are Sources of Extensively- and Multidrug-Resistant KPC- and OXA-48-Producing Enterobacteriaceae in Coastal Marine Environment - Kvesić, Marija; Šamanić, Ivica; Novak, Anita; Fredotović, Željana; Dželalija, Mia; Kamenjarin, Juraj; Goić Barišić, Ivana; Tonkić, Marija; Maravić, Ana (Frontiers in Microbiology, 2022)
The rapid and ongoing spread of carbapenemase-producing Enterobacteriaceae has led to a global health threat. However, a limited number of studies have addressed this problem in the marine environment. We investigated their emergence in the coastal waters of the central Adriatic Sea (Croatia), which are recipients of submarine effluents from two wastewater treatment plants. Fifteen KPC-producing Enterobacteriaceae (9 E. coli, 4 Klebsiella pneumoniae and 2 Citrobacter freundii) were recovered, and susceptibility testing to 14 antimicrobials from 10 classes showed that four isolates were extensively drug resistant (XDR) and two were resistant to colistin. After ERIC and BOX-PCR typing, eight isolates were selected for whole genome sequencing. The E. coli isolates belonged to serotype O21:H27 and sequence type (ST) 2795, while K. pneumoniae isolates were assigned to STs 37 and 534. Large-scale genome analysis revealed an arsenal of 137 genes conferring resistance to 19 antimicrobial drug classes, 35 genes associated with virulence, and 20 plasmid replicons. The isolates simultaneously carried 43 to 90 genes encoding for antibiotic resistance, while four isolates co-harbored carbapenemase genes blaKPC-2 and blaOXA-48. The blaOXA-48 was associated with IncL-type plasmids in E. coli and K. pneumoniae. Importantly, the blaKPC-2 in four E. coli isolates was located on ~40 kb IncP6 broad-host-range plasmids which recently emerged as blaKPC-2 vesicles, providing first report of these blaKPC-2-bearing resistance plasmids circulating in E. coli in Europe. This study also represents the first evidence of XDR and potentially virulent strains of KPC-producing E. coli in coastal waters and the co-occurrence of blaKPC-2 and blaOXA-48 carbapenemase genes in this species. The leakage of these strains through submarine effluents into coastal waters is of concern, indicating a reservoir of this infectious threat in the marine environment.